IN VITRO ANTITUMOR ACTIVITY OF PATULIN ON LİVER AND LUNG CANCER CELL LINES - Yüce, Hande; Türkmen, Neşe Başak; Şenkal, Selinay; Özek, Dilan Aşkın; Bulut, Ezgi; Doğan, Ayşegül; Ünüvar, Songül (University of Ankara, 2022)
Objective: Patulin is a mycotoxin produced by some molds, mainly Aspergillus and Penicillium, and is responsible for mycotoxicosis in animals and humans. Although there are still no detailed data on the antitumor activity of patulin, some reports indicate that it induces cellular apoptosis and toxicity. Our aim in this study is to determine the antiproliferative and antimigration effects of patulin on human liver and lung cancer cells and its effect on gene expressions in apoptotic pathways. Material and Method: HEP3B and A549 cell lines were used to determine the efficacy of patulin in the treatment of liver and lung cancers. Cell lines were exposed to increasing concentrations of patulin (1, 2.5, 5, 10, 25, 50, and 100 µM), followed by determination of cell viability, cell migration, and apoptosis by MTS assay, wound healing assay, and RT-PCR assays. Result and Discussion: Patulin caused a dose-dependent significant decrease in cell viability and cell migration in both cancer cell lines. It also promoted the induction of apoptosis in both cell lines. Our results showed that patulin can significantly reduce tumor growth in human liver and lung cancer cells in vitro. © 2022 University of Ankara. All rights reserved.
PATULİNİN KARACİĞER VE AKCİĞER KANSERİ HÜCRE HATLARI ÜZERİNDEKİ İN VİTRO ANTİTÜMÖR AKTİVİTESİ
Keywords: A549; apoptosis; cancer; HEP3B; mycotoxin; patulin